Laser processing of multiple surface characteristics for Ti6Al4V biomedical implants. Issue 3 (17th February 2021) - Ghate, Nakul D; Shrivastava, Amber
ABSTRACT: Surface roughness, microhardness, and wettability are the surface characteristics which significantly influence the implant performance. Laser surface modification with raster scan is a well-known technique for processing the material surfaces. This technique has potential to modify multiple surface characteristics together. However, multiple process parameters are involved and each parameter can affect individual surface characteristics differently. This work focuses on processing multiple surface characteristics (surface roughness, micro-hardness, and wettability) with laser surface modification. Laser surface modification of Ti6Al4V is performed with wide range of process parameters. The laser modified samples are characterized, and surface roughness, microhardness, and wettability are measured. A modified heat input parameter is introduced, which accounts for multiple LSM process parameters. The range of the modified heat input parameter for various implants are identified, by superimposing the modified heat input parameters for experiments against the surface requirements of implants, on the Ashby styled three-dimensional projection plot. Comparable combinations of surface characteristics are achieved from different combinations of the process parameters with similar modified heat input parameters. This study shows that multiple surface characteristics can be processed together to meet implant specific requirements and full potential of the laser surface modification process can be utilized.